Gender Inequality In Education and Its Impact On Poverty In Indonesia From 2012-2021 - Agnes Nabila; Hera Susanti (PT Publikasiku Academic Solution, 2025)
The condition of gender equality in education in Indonesia is an issue that continues to make progress, although it is not yet aligned with the global gender equality situation. Based on the Global Gender Gap Index (GGGI) in 2021, Indonesia still ranks 101 out of 156 countries with a score of 0.688 or 68.8 percent gender equality. Indonesia's ranking in the GGGI sub-index, particularly in educational attainment, is relatively lower. This research examines the condition of gender inequality in education and its impact on poverty in Indonesia at the district/city level. By using panel data from 2012 to 2021, the analysis reveals variations in gender disparities in education across different districts/cities. The research findings show a significant negative relationship between gender inequality in education, measured by the ratio of average years of schooling for females compared to males, and the poverty indicator, indicating that an increase in gender equality in education can contribute to poverty alleviation efforts. The research emphasizes the importance of a contextual approach to address specific challenges and opportunities in different regions. Policy recommendations include promoting gender equality in education, eliminating gender stereotypes, and considering factors such as economic growth, population size, internet access, and social assistance programs in poverty alleviation efforts. This research is expected to contribute to policy-making efforts to achieve gender equality and poverty reduction in Indonesia